Disaster Resilient and Responsive Public Financial Management : An Assessment Tool (Washington, DC: World Bank, 2022)
The Disaster Resilient and Responsive Public Financial Management (DRR-PFM) Assessment is designed to help countries strengthen the capability of their Public Financial Management (PFM) systems to prepare for, respond to, and recover from disasters. The DRR-PFM Assessment expands upon an analytical tool first developed to support resilience in nine Caribbean countries. The updated framework integrates ex-ante risk reduction explicitly; it considers how central finance agencies can use risk analysis to inform their risk reduction, response, and recovery planning. The DRR-PFM Assessment identifies opportunities for reforms to laws, regulations, policies, and systems that can strengthen a country’s capacity to manage disaster-related risks and sustain PFM functions after a disaster. Successive DRR-PFM assessments can track reform implementation.